THE ROLE OF BUMDES ADMINISTRATORS IN MANAGING THE BUMDES RIVER TOURISM "CAFE KALITIKUNG" IN TAMBAKCEMANDI VILLAGE, SEDATI DISTRICT, SIDOARJO REGENCY - Rizal, Ahmad; Rodiyah, Isnaini (Journal of Economic and Economic Policy, 2025)
Objective: This study aims to determine and analyze the role of BUMDes administrators in managing the “Cafe Kalitikung” River Tour in Tambakcemandi Village, Sedati District, Sidoarjo Regency. Method: Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. Data analysis follows the Miles & Huberman framework: collection, reduction, presentation, and drawing conclusions. Results: Based on Edy Suhardono's role theory, administrators act as facilitators, drivers, and regulators. Facilitators provide infrastructure such as piers and tourism facilities. Drivers involve local resources and raise environmental awareness. Regulators establish operational policies for sustainable management. Despite challenges in management, human resources, and funding, collaboration between the village government, community, and BUMDes administrators highlights the potential of “Kafe Kalitikung” as a village economic model. Novelty: Despite challenges in management, human resources, and funding, collaboration between the village government, community, and BUMDes administrators highlights the potential of “Kafe Kalitikung” as a village economic model.